COMPARISON OF MODELS AND ESTIMATION OF MISSING PARAMETERS OF SOME MATHEMATICAL MODELS RELATED TO IN SITU DRY MATTER DEGRADATION - F. Uckardes; M. Korkmaz; P. Ocal (Journal of Animal and Plant Sciences, 2013)
The aim of this study was to estimate missing parameters of the models such as the Orskov, Gompertz, Logistic and Richard models. These missing parameters for some models were estimated on the rapidly soluble fraction, the insoluble but potentially degradable fraction and the partial potentially degradable fraction. No difference was found among the values of these parameters (P>0.05), except for the constant rate of degredation. Besides, other missing parameters of the models studied were: partial dry matter disappearance in rumen for the percent rate at time t (tp) and Rtp, rate of the partial dry matter disapparance in rumen at the time tp (t0, t25, t50, t75 and t95). These values and formulas for these values in different time intervals were also obtained. The second objective was especially on the comparison of the results of all tp`s (t25, t50, t75 and t95) and Rtp`s (Rt0, Rt25, Rt50, Rt75 and Rt95) in the models. The results of all tp`s and Rtp`s in the models were compatible with each other (P>0.05). The thirth objective was to investigate the fit performance of the models for in situ degradation studies. Some criteria used with the purpose of evaluating performances of models studied were on the analysis of residual (The Runs test and Durbin Watson) and goodness-of-fit (Residual Mean Square, the coefficient of determination and F-ratio). As a result of this study, while the Orskov model showed the best statistical performance and goodness of fit, the Richard model showed the worst. it is determined that the Gompertz model showed a systematic deviation from the data and is not appropriate for describing in situ data.
Keywords: in situ degradation; mathematical models; exponential shape; sigmoidal shape